2012
DOI: 10.1159/000336388
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Can f 5 in a Case of Human Seminal Plasma Allergy

Abstract: Background: The existence of IgE binding to dog dander extract without IgE antibodies against the described dog allergens (Can f 1, 2, 3 and 4) implies the presence of other dog allergens yet to be identified. Recently, an IgE-binding protein was isolated from dog urine and identified as prostatic kallikrein; it has been named Can f 5. Cross-reactivity between a dog dander allergen and human prostate-specific antigen (PSA) has been described. The aim of this study was to identify the dog dander allergen that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…Cross-reactivity of this allergen with the newly identified dog dander allergen Can f 5 appears to be clinically relevant [41]. …”
Section: Triggers and Mechanismsmentioning
confidence: 99%
“…Cross-reactivity of this allergen with the newly identified dog dander allergen Can f 5 appears to be clinically relevant [41]. …”
Section: Triggers and Mechanismsmentioning
confidence: 99%
“…Some studies have highlighted the increasing importance of allergic sensitization to Can f 5 (a kallikrein), which is an androgen-regulated protein expressed in the prostate and detectable only in male dogs (small amounts might also be present in dog epithelia). In addition, Can f 5 may be involved in human seminal plasma allergy [7]. Schoos et al [8] recently suggested that patients monosensitized to Can f 5 seem to tolerate female dogs.…”
Section: To the Editormentioning
confidence: 99%
“…8 Moreover, few dog dander allergens demonstrate cross-reactivity with an allergic protein in human seminal plasma. 9,10 Furthermore, it has been hypothesized that an infection by microorganisms that introduce cross-reacting antigens may also result in the production of anti-sperm antibodies. 11 Levine et al have revealed that the causative antigen, which is a small protein, seems ubiquitous in the human prostatic secretion.…”
Section: Introductionmentioning
confidence: 99%